Analisis Motivasi Belajar Mahasiswa Terhadap Pembelajaran Online - Nurullah Sururi Afif nurullah; Putie Maharani Basa; Anantha Zakharia (Publikasi Indonesia, 2022)
During the pandemic, face-to-face learning activities are reduced or even eliminated. Teaching and learning activities at schools and campuses are carried out online, where the teaching and learning process between educators and students is carried out through the internet network. In tertiary institutions, online learning is also applied. Changes in teaching and learning activities that were previously carried out face-to-face to online, of course, are a challenge for lecturers and students. With the implementation of online learning, adjustments in various ways must be made. The research was conducted on students of Bina Sarana Informatika University, Slipi Campus. Online learning activities are welcomed by students, where online lectures make students more comfortable studying because they are done at home and students feel more independent in learning when online lectures